DINAMIKA KOMUNIKASI ORGANISASI RADIO REPUBLIK INDONESIA STUDIO PENYIARAN (RRI SP) KABUPATEN BONE - Ratnawiyah Bahar (Jurnal Dakwah Tabligh, 2020)
This study aimed to describe the flow of communication in the organization of Radio Republik Indonesia (RRI) Bone district. The results showed that 1) the communication vertically downward (downward communication) performed in Studio Broadcast Radio Republik Indonesia (RRI SP) Bone district, this communication between leaders and subordinates formally, or informally communicated and the associated jobs. As formally this is to conduct a meeting with the members face to face gives suggestions - suggestions or inputs. 2) Communication organization vertically upward (upward communication) will be undertaken in Studio Broadcast Radio Republik Indonesia (RRI SP) Bone district, it can be seen that the leaders hear or know of inputs or suggestions from subordinates. 3) Communication horizontally Studio Broadcast Radio Republik Indonesia (RRI SP) Bone regency implement the types of formal and informal communication, regard being communicated about one's job, sharing, mutual support. Formal communication takes place the official exchange of information took place. In addition to formal communication also takes place informally, were developing social relations among employees.